“An Experimental Study to Assess the Effectiveness of Planned Teaching Program Regarding Sex Education and Menstrual Hygiene among Students in Selected Secondary School of Ahmednagar, District” - Rajesh Salvi, Jayashree; Naik, Shweta (International Journal of Nursing Research, 2023)
Aim: The aim of this study was to evaluate the effectiveness of planned teaching program regarding sex education and menstrual hygiene. Materials and Methods: In the present study, the investigator selected the quasi-experimental design with evaluatorry approach research design, keeping in the view of objectives of the study. A study was conducted in Somaiya Vidyamandir School, Sakharwadi, Ahmednagar district. A study was done on 123 students of Somaiya Vidyamandir School, Sakharwadi. In all boys were 64 and girls were 59. In this study, convenient sampling technique was used. Data were collected using a structured knowledge questioner. The student who were available at the time of data collection and who knew Marathi language and were willing to participate in the study were only included for the data collection. Data were analyzed using descriptive statistics. Result: knowledge of girls in pre-test and post-test. Knowledge gain regarding what to be used during menstrual cycle is 50%. Knowledge gain regarding how many times sanitary pads to be changed every day was 60%. Gain in knowledge regarding how many times to wash perineum is 60%. Knowledge gain regarding how to dispose the used sanitary pads or clothes during menstrual cycle is 70% which is maximum. Conclusion: Subjects had improvement in knowledge regarding sex education and menstrual hygiene. Sex education and menstrual hygiene session was beneficial for the subjects as they were taught how to maintain hygiene, which will ultimately help the students. Hence, it conclude that planned teaching program is effective.